Efeito de intermediários do ciclo de krebs sobre alterações oxidativas induzidas por diferentes agentes oxidantes - Puntel, Robson Luiz (2006)
Recent data from the literature have suggested that some Krebs cycle intermediates could act as potent antioxidant agents, both in vitro and in vivo, against a variety of pro-oxidant agents. However, the mechanism(s) involved in the antioxidant effect of Krebs cycle intermediates are not fully understood. Additionally, there are scarce data in the literature taking into account the in vitro effect of Krebs cycle intermediates during oxidative stress conditions. Thus, the aim of this study was to determine the effect of some Krebs cycle intermediates on lipid peroxidation induced in vitro by different pro-oxidant agents, and the mechanism(s) by which they act. Firstly, we investigated the effect and the mechanism(s) by which malonate and quinolinic acid modulate the thiobarbituric acid- reactive species (TBARS) production in vitro, using rat brain S1 preparations (Article 1). The present results showed that the malonate-induced TBARS production was not changed by potassium cyanide or MK-801. However, the pro-oxidant effect of quinolinic acid was significantly prevented by MK-801. In addition we found that malonate was able to form complexes with iron ions (Fe2+), but these complexes were not able to interfere with in vitro deoxyribose degradation assays. Based on the results presented, we conclude that malonate pro-oxidant activity in vitro seems to be independent of the NMDA receptors activity. Additionally, we suggest that the malonate effect, in these conditions, is due to its ability to form complexes with iron ions, thus modulating an adequate ratio Fe2+/Fe3+ that could cause an increase in free radicals generation. In contrast, the quinolinic acid effect seems to be dependent of the NMDA receptors activation. However, we can not rule out the involvement of iron ions in quinolinic acid toxicity under our assay conditions. An other objective of this study was to investigate the effect of some Krebs cycle intermediates on quinolinic acid- or iron (Fe2+)-induced TBARS production in the rat brain S1 preparations, and the mechanism(s) by which they act (Article 2). The results showed that oxaloacetate, citrate, succinate, and malate were able to significantly prevent both basal and quinolinic acid- or iron-induced TBARS production. However, α-ketoglutarate induced per se a significant increase in basal TBARS production. The addition of potassium cyanide or the heat-treatment of S1 at 100ºC during 10 min completely abolished the antioxidant succinate activity, without change the effect of other Krebs cycle intermediates studied. Except for succinate, all intermediates used in this study were able to form complexes with iron (Fe2+) ions, however only oxaloacetate and α-ketoglutarate significantly prevented deoxyribose degradation induced by hydrogen peroxide. Based on the results presented, we concluded that oxaloacetate, malate, succinate, and citrate could act as antioxidants under basal, and under quinolinic acid- or iron- induced TBARS production, whereas α-ketoglutarate act as a pro-oxidant agent per se. The mechanism(s) by which citrate, malate, and oxaloacetate acts seems to be related to their ability to form complexes with iron (Fe2+) ions, thus modulating the iron redox cycle. In contrast, the succinate antioxidant effect seems to be dependent of the succinate dehydrogenase (SDH) activity.